The Effect of Celebrity Endorsement on Instagram Fashion Purchase Intention: The Evidence from Indonesia - Herjanto, Halimin; Adiwijaya, Michael; Wijaya, Elizabeth; Semuel, Hatane (Organizations and Markets in Emerging Economies, 2020)
To maintain the significantly positive influence of celebrity endorsement (CE) on Instagram user consumption behavior, scholars and business practitioners are motivated to have a better understanding of this phenomenon. Literature on CE focuses on its direct effect on attitude toward various brand components; however, this study takes a different approach by developing a new conceptual model and a set of hypotheses that aims to generate a better picture of the relationship between two brand components (brand image and brand trust) and repurchase intention. The present study also examines the moderating role of CE in the relationship between brand image and brand trust as well as repurchase intention.The hypotheses were tested using online survey data from 220 Indonesian respondents. To test the theoretical model, this study employs ordinary least square regression (OLS), as well as Baron and Kenny’s (1986) method to test moderating hypotheses. The results show that the hypothesized model of CE on brand image, brand trust and repurchase intention fits the data. In addition, the findings also demonstrate that CE moderates the relationship between brand image and brand trust, and between brand image and repurchase intention.The findings offer important contributions to the academic by enriching the body of literature on online consumption behavior. They reveal the moderating effect of CE, and potentially inspire scholars to conduct further research. To business practitioners, this study suggests the importance of engaging with celebrities to endorse their brands. At the same time, to avoid the risk of reverse image, managers are recommended to think carefully about which celebrities are suitable to represent their brands.
Keywords: celebrity endorsement; brand image; brand trust; purchase intention